Optical and photoluminescent properties of nanostructured hybrid films based on functional fullerenes and metal nanoparticles - Dmitruk, N.; Borkovskaya, O.; Naumenko, D.; Berezovska, N.; Dmitruk, I.; Meza-Laguna, V.; Alvarez-Zauco, E.; Basiuk, E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The chemically cross-linked C₆₀ thin films, capable of binding Ag or Au
nanoparticles, were prepared by the gas-phase treatment with diamine for one set of
samples and dithiol for another one and decoration with Ag or Au nanoparticles,
respectively. The optical and photoluminescent properties of the obtained nanostructured
hybrid films in comparison with the undecorated films were studied. The low
temperature photoluminescence (PL) spectra demonstrate significant changes of the band
intensity and appearance of fine structure for bands connected with radiative transitions
of self-trapped and localized excitons. The decoration of pristine and treated C₆₀ films
with Ag nanoparticles leads to a decrease of PL intensity and to slight bandgap reduction.
These phenomena can be explained by the increase of the surface recombination velocity
at the fullerene-nanoparticle interface. At the same time, the nanoparticles insignificantly
decrease the transmittance of light into the fullerene and Si layers, and have almost no
influence on photoelectric properties of metal/fullerene/Si barrier structures.